Social Seme as Component of Meaning in Names of Internet communities - A. N. Blinova (Научный диалог, 2017)
The designations “groups” and “communities” are examined as those given to associations of communicants on the Internet. The author states that the names of these associations have certain pragmatic tasks, since they are attracting the attention of Internet users and work on the expansion of groups. It is proved that the solution of such problems led to social semes in the names of unions. The author believes that the onomastic linguistic material (proper nouns) is also the part of social vocabulary. Social lexis refers to many words and expressions that serve as the designations of objects and phenomena of the life of society and a man because of his social characteristics - status, roles, etc. The relevance of the study is justified by the fact that there are no ideographic description of the social vocabulary in the Russian language and the concept of such a description. Analysis of the composition ofthe names of Internet communities allows to draw some conclusions regarding the features of group Internet communication. It is shown that the names of Internet communities are their hallmarks, that indicate the range of interests of participants of virtual communication in each group and the perception of social realities. The classification of categories depending on the method of education is given. It is concluded that many of the names include lexemes that characterize man from the standpoint of his social function.